Universities and the Production of Elites Discourses, Policies, and Strategies of Excellence and Stratification in Higher Education (Palgrave Studies in Global Higher Education,, 2018)
This book explores how universities as organizations influence and construct the production of academic elites and elitist institutions. It analyzes the role played by the reorganization of higher education (HE) institutions, stimulated by new performance-based narratives aimed at building attractiveness towards stakeholders such as governments, prospective employers, academics, and students. Based on American, European, and Asian case studies of HE systems and institutions considered at various scales, the volume analyzes the consequences of increasing competition between HE institutions which are facing challenges such as the internationalization of higher education supply, the shortage of public resources and the structural changes of labor market demands. It argues that policy discourses and tools, as well as assessment devices such as rankings and accreditation, incentivize HE institutions to develop positioning strategies that contribute to stratification and the production of elites. It will be of great interest to students and researchers in the fields of higher education, sociology, and education policy.